2007
DOI: 10.1897/06-119r.1
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity ranking of estuarine sediments on the basis of Sparus aurata biomarkers

Abstract: Sparus aurata biomarkers were used to rank sediments from the Sado River estuary (Portugal) according to their toxicity. Initially, the activities of liver ethoxyresorufin-O-deethylase, liver and gill glutathione S-transferases, muscle lactate dehydrogenase, and brain acetylcholinesterase were tested in a laboratory bioassay with the reference compound benzo[a]pyrene. Enzymatic activities were determined in different tissues of fish exposed for 48, 96, or 240 h to three concentrations of benzo[a]pyrene (25, 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Subsequent to anesthetizing in benzocaine (150 ppm, Mondon et al 2001) or tricaine methanesulfonate (MS-222) solution, fish are sacrificed for the evaluation of selected mechanistic-based endpoints. The endpoints cover acute and long-term toxicity, bioaccumulation, endocrine effects, carcinogenicity and mutagenicity, and toxic effects on reproduction (Bucke et al 1989;Roberts et al 1989;Ankley 1991;Almeida et al 2005;Inzunza et al 2006;Jimenez-Tenorio et al 2007; Barbee et al 2008;Cunha et al 2007;Costa et al 2008; Table 1). Over the period of use of these techniques, laboratory studies with bulk sediments have indicated that many samples from numerous locations exhibit acute and/or chronic toxicity to a variety of test species.…”
Section: Selection Of Exposure Scenariomentioning
confidence: 99%
See 3 more Smart Citations
“…Subsequent to anesthetizing in benzocaine (150 ppm, Mondon et al 2001) or tricaine methanesulfonate (MS-222) solution, fish are sacrificed for the evaluation of selected mechanistic-based endpoints. The endpoints cover acute and long-term toxicity, bioaccumulation, endocrine effects, carcinogenicity and mutagenicity, and toxic effects on reproduction (Bucke et al 1989;Roberts et al 1989;Ankley 1991;Almeida et al 2005;Inzunza et al 2006;Jimenez-Tenorio et al 2007; Barbee et al 2008;Cunha et al 2007;Costa et al 2008; Table 1). Over the period of use of these techniques, laboratory studies with bulk sediments have indicated that many samples from numerous locations exhibit acute and/or chronic toxicity to a variety of test species.…”
Section: Selection Of Exposure Scenariomentioning
confidence: 99%
“…But how are test fish species selected? The primary criteria for fish species selection should be the species' ecological and/or economical importance to the region (e.g., Rhombosolea tapirina in Mondon et al 2001, Oncorhynchus kisutch in Barbee et al 2008; Sparus aurata in Cunha et al 2007) and its relative sensitivity to sediment contamination (e.g., S. maximus in Kilemade et al 2009). Other factors should also be considered including the ease of collection (or purchasing), convenient size, adaptation in laboratory (ease of handling), lifestyle (benthic or pelagic), indigenous to research site or closely related to an indigenous species (Cheung et al 1997;Guy et al 2006).…”
Section: Selection Of Fish Speciesmentioning
confidence: 99%
See 2 more Smart Citations
“…There are well reported problems associated with these techniques like strong distortions (called the horseshoe effect) caused by long gradients (Kenkel and Orlóci 1986;Swan 1970) for PCA and redundancy analysis-RDA; the arch effect caused by the erroneous attribution of low Chi square distances to sites with no species in common (Gauch 1982) for CA and CCA; and problems with predefinition of dimensionality, local minima, meaningless axes and confusion of location and dispersion, besides the problem of not, really, use the species' quantitative data for NMDS (Brayard et al 2007;Brehm and Fiedler 2004;Cunha et al 2007;Legendre and Legendre 1998;Warton et al 2012).…”
Section: Introductionmentioning
confidence: 99%